2013
DOI: 10.3109/00016489.2013.799293
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous bone-conduction hearing device: audiological and surgical aspects in a first series of patients with mixed hearing loss

Abstract: The surgical procedure was completed in all cases, with only minor intraoperative divergence from the CT-based planning and no postoperative complications. The average improvement of the SRT in quiet with the BB in comparison to the unaided condition was 36.25 dB. All the implanted subjects reached SRT values below 65 dB, indicating a better understanding in quiet, with 100% word recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
1
10

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 11 publications
7
52
1
10
Order By: Relevance
“…The authors found improved word recognition scores at activation and continued to see improvement up to 3 months after activation. Similarly, Barbara et al [13] noted an improvement in SRT and word recognition scores compared to the unaided sound field condition. Both studies found no changes in unaided air or bone conduction thresholds postoperatively.…”
Section: Surgery and Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors found improved word recognition scores at activation and continued to see improvement up to 3 months after activation. Similarly, Barbara et al [13] noted an improvement in SRT and word recognition scores compared to the unaided sound field condition. Both studies found no changes in unaided air or bone conduction thresholds postoperatively.…”
Section: Surgery and Outcomesmentioning
confidence: 99%
“…Patients must have appropriate bone thickness and consistency to accommodate the internal device, as determined by a preoperative CT scan [14 • ]. Unlike the Cochlear and Oticon Medical devices, the Bonebridge does not require osseointegration [13]. The Bonebridge is MRI compatible up to 1.5 T [13].…”
Section: Clinical Indicationsmentioning
confidence: 99%
See 3 more Smart Citations